The contribution of negotiation of meaning to language accuracy in an EFL setting through a focused task - Flora Flora; Mahpul Mahpul; Muhammad Sukirlan (Universitas Syiah Kuala, 2021)
Despite the extensive research on the negotiation of meaning (NoM) using unfocused tasks, to our knowledge no study portrays to what extent NoM contributes to learners’ language accuracy, grammar, and vocabulary, in particular, using a focused task. Therefore, this research set out to obtain in-depth information about the contribution of NoM to language accuracy when learners were assigned to engage in a focused task discussion. The participants, treated as three dyads based on their English proficiency, were taken purposely from one class of the sixth-semester students in the Department of English Education in the Faculty of Education at Universitas Lampung, Indonesia. They were paired based on their English abilities (high-high; high-low; low-low) and their intimates among the 24 students in the class. All their utterances produced during a fifteen-minute focused task discussion were recorded and analyzed following the theory of NoM and language accuracy. It was discovered that the learners were engaged in NoM during the focused task discussion, and it contributes to the students’ language accuracy. Therefore, to optimize the contribution of NoM to language accuracy, the topic to be discussed should be based on the learners’ output (focused task) since the interlocutor can offer assistance as part of the negotiation of meaning process. The suggestions for future research are also discussed.